Analysis of Effectiveness and Efficiency Factors Affecting Boarding House Selection Preferences in Malang City - Abbas Syarif Hidayatullah; Adji Seputro; Alfin Yuan Octavedha; Ike Susanti (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Boarding houses are expanding rapidly in many cities in response to lifestyle changes and the growing need for practical accommodation among economically active groups. Their residents generally include employees, students, and self-employed individuals who rent rooms based on diverse considerations. This study analyzes the effectiveness and efficiency of boarding-house operations in Malang City in relation to residents' service satisfaction. A descriptive design combining qualitative and quantitative approaches was employed. Data were obtained by converting information weights from survey results and structured interviews with 136 purposively selected respondents known to the researchers. All respondents were male boarding-house residents in Malang City. The effectiveness predictors were ambience, room condition, security, and garage availability, whereas the efficiency predictors were accessibility, electricity, water, and internet access (Wi-Fi). The qualitative analysis used a gap-analysis (shift-share) approach combined with an Ishikawa diagram, while the quantitative analysis used SPSS to estimate a regression model. The findings indicate that security was the residents' primary consideration regarding effectiveness, while accessibility was their primary consideration regarding efficiency.